2013
DOI: 10.4172/1747-0862.1000061
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Copy Number Variation in African Americans with Type 2 Diabetes-Associated End Stage Renal Disease

Abstract: This study investigated the association of copy number variants (CNVs) in type 2 diabetes (T2D) and T2D-associated end-stage renal disease (ESRD) in African Americans. Using the Affymetrix 6.0 array, >900,000 CNV probes spanning the genome were interrogated in 965 African Americans with T2D-ESRD and 1029 non-diabetic African American controls. Previously identified and novel CNVs were separately analyzed and were evaluated for insertion/deletion status and then used as predictors in a logistic regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…( 13 ) and to the copy number gain defined by Cooke Bailey et al . ( 12 ). Detailed read-depth and long-PCR characterization of AMY2A deletions, corresponding approximately to CNVR266.9 of Conrad et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 13 ) and to the copy number gain defined by Cooke Bailey et al . ( 12 ). Detailed read-depth and long-PCR characterization of AMY2A deletions, corresponding approximately to CNVR266.9 of Conrad et al .…”
Section: Resultsmentioning
confidence: 99%
“…It is not clear why these views of AMY1 variation differ, and, in particular, whether the failure of real-time PCR studies to detect a preponderance of even numbers reveals a limitation of their accuracy, or whether the predominantly odd-numbered haplotypes observed in early studies represented a misleading sample. Furthermore, although most attention has focussed on AMY1 CNV, there have been reports of variation in copy number of the pancreatic AMY2A / 2B genes ( 3 , 7 , 12 , 13 ); however, the high-sequence identity between AMY1 and AMY2 genes makes resolving these CNVs unusually difficult, and these AMY2 variants, and their relationship to AMY1 variation, have not been clearly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Primarily because of its early discovery and extensive range, most attention on amylase CNVs has focussed on the salivary amylase gene AMY1 , but there have been reports of CNVs involving the AMY2 genes [Groot et al., ; Conrad et al., ; Sudmant et al., ; Cooke Bailey et al., ]. Integration of information from read‐depth analysis, segregation, and direct typing of copy number demonstrated haplotypes harboring even numbers of AMY1 in conjunction with CNVs of the pancreatic amylase genes AMY2A and AMY2B .…”
Section: Introductionmentioning
confidence: 99%
“…The leucine-rich repeat and Ig domain–containing 2 gene is expressed in neuronal tissue, and rs10968576 have been associated with body mass index3839. This study also revealed CNV at 1p21.1 affecting AMY2B gene known to be associated with type 2 diabetes mellitus40. The pancreatic alpha-amylase gene codes for a protein that catalyzes the initial step in digestion of dietary starch and glycogen.…”
Section: Discussionmentioning
confidence: 58%